Regimes of cannibality: A Peripheral Perspective on War, Colonization and Culture (2011)
The present article aims at postulating cannibalism as a fundamental axis for the analysis of the processes of subjectivation of Spanish America since the 15th century. The hypothesis is that this process has gone through three stages, which allow for the delimitation of the differences of what I shall refer to, for now, as regimes of cannibalism understood as subjectivation processes: (i) Anthropophagic or of ritual war. (ii) Mimetic or of colonial incorporation (iii) Iconic or of mediatic absorption, at a global level. In order to construct the regimes of cannibalism as a concept I have chosen to use two perspectives: the one which speaks of the ritual experimentation of anthropophagy from the inside and the one which moves through the variants of that double desire for the other’s desire that makes every process of colonization possible; in the known forms of territorial annexation, incorporation (productive, spiritual, institutional) and absorption by the global system of mediatization.